Geochemistry of hydrothermal vent fluids and its implications for subsurface processes at the active Longqi hydrothermal field, Southwest Indian Ridge. (April 2017) - Ji, Fuwu; Zhou, Huaiyang; Yang, Qunhui; Gao, Hang; Wang, Hu; Lilley, Marvin D.
Abstract: The Longqi hydrothermal field at 49.6°E on the Southwest Indian Ridge was the first active hydrothermal field found at a bare-rock ultra-slow spreading mid-ocean ridge. Here we report the chemistry of the hydrothermal fluids, for the first time, that were collected from the S zone and the M zone of the Longqi field by gas-tight isobaric samplers by the HOV "Jiaolong" diving cruise in January 2015. According to H2, CH4 and other chemical data of the vent fluid, we suggest that the basement rock at the Longqi field is dominantly mafic. This is consistent with the observation that the host rock of the active Longqi Hydrothermal field is dominated by extensively distributed basaltic rock. It was very interesting to detect simultaneously discharging brine and vapor caused by phase separation at vents DFF6, DFF20, and DFF5 respectively, in a distance of about 400 m. Based on the end-member fluid chemistry and distance between the vents, we propose that there is a single fluid source at the Longqi field. The fluid branches while rising to the seafloor, and two of the branches reach S zone and M zone and phase separate at similar conditions of about 28–30.2 MPa and 400.6–408.3 °C before they discharge from the vents. The end-member fluid compositions of these vents are comparable with or within the range of variation of known global seafloor hydrothermal fluid chemical data from fast, intermediate and slow spreading ridges, which confirms that the spreading rate is not the key factor that directly controls hydrothermal fluid chemistry. The composition of basement rock, water-rock interaction and phase separation are the major factors that control the composition of the vent fluids in the Longqi field. Highlights: Liquid and vapor phase fluids after phase separation were observed at the same time. A single source fluid that branches and phase separates is suggested. It is suggested that the basement rock at the Longqi field is mafic.